Diseño de la portada y la comercialización del diario La Hora en el cantón Quevedo, año 2019 - Quimis Peñafiel, Raquel Felisa (2020)
The present research project called written resignation of the complex exam will cover a topic of great relevance in terms of the design of the cover in the commercialization of the newspaper “La Hora” in the city of Quevedo specifically, addressing important aspects such as design, content, images, body structure and dimensions of it For the development of the research there will be the structure or body of the detailed project of two chapters in which they will deploy the respective methodological framework, in which the subject of the case to be treated will be defined, followed by the approach of the problem, it will also be raised The general theme with its respective justification will also be formulated in a very correct way the general objective followed by the specific ones, to direct the investigation process. In addition, during the development of the investigation, possible solutions for the problem found during the field inquiry obtained through the surveys carried out to the citizens of Quevedeña as well as to the people who work in the newspaper La Hora de la ciudad de Quevedo In addition, the respective conclusions and recommendations were generated to terminate the research project reaching the objectives set for the benefit of the parties involved in the case.